2012
DOI: 10.4103/0974-2077.104911
|View full text |Cite
|
Sign up to set email alerts
|

Chemical peels for acne and acne scars in asians: Evidence based review

Abstract: Chemical peeling is a widely used procedure in the management of acne and acne scars, but there are very few studies on Asian populations who are more prone to develop hyper pigmentation. This article aims to summarize and evaluate the existing studies on the role of chemical peels in the treatment of acne and acne scars among Asians. An online search was conducted to identify prospective studies published in English that evaluated the use of chemical peels in active acne and acne scars in Asian populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 26 publications
(48 reference statements)
0
36
0
7
Order By: Relevance
“…In a review of acne and acne scar management, superficial chemical peels in Asians were considered an adjuvant therapy for all forms of acne, leading to a faster clinical response and patient satisfaction . Treatments with 30% salicylic acid (SA) and 35–70% GA were considered efficient for reducing inflammatory and noninflammatory acne lesions in Asians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a review of acne and acne scar management, superficial chemical peels in Asians were considered an adjuvant therapy for all forms of acne, leading to a faster clinical response and patient satisfaction . Treatments with 30% salicylic acid (SA) and 35–70% GA were considered efficient for reducing inflammatory and noninflammatory acne lesions in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Jessner solution has been shown to be as effective as 70% GA, but the exfoliation caused by the first one has dissatisfied some patients. The combination of SA and mandelic acid peels has demonstrated better results than 35% GA …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that chemical peels were good adjuvants for treatment of acne and acne scars, especially 30% salicylic acid and 35-70% glycolic acid for both inflammatory and non-inflammatory lesions of acne. [1] Elsewhere in the issue, Sarkar et al . review chemical peels for melasma in dark-skinned patients.…”
mentioning
confidence: 99%